2017
DOI: 10.20471/apr.2017.53.01.04
|View full text |Cite
|
Sign up to set email alerts
|

The role of thrombocyte serotonin system and some thrombocyte characteristics in treatment of depressive patients with cardiovascular diseases

Abstract: -Serotonin has an important role in the development of depressive disorders. Bearing in mind that direct testing of central nervous system is unavailable to researchers due to the inability to reach the samples, ever greater attention is given to the peripheral systems that can help us diagnose and detect changes of the disease, but also follow the course of its treatment and recovery. Thrombocyte is a blood cell that contains serotonin lodged in its delta granules. Thrombocyte serotonin system is similar, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The platelet 5‐HT system bears some similarities to the serotonergic synapses in the CNS with regard to the storage, accumulation, and release of 5‐HT (Stahl, 1977). In spite of those similarities, these two systems differ concerning metabolizing enzymes, and platelets are not competent to synthesize 5‐HT because of the absence of tryptophan hydroxylase (Kostanjšak & Zdunić, 2017; Stahl, 1985). In consideration of psychopathology, previous studies have shown lower 5‐HT levels in the platelets of patients suffering from depression (Kostanjšak & Zdunić, 2017; Maurer‐Spurej et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The platelet 5‐HT system bears some similarities to the serotonergic synapses in the CNS with regard to the storage, accumulation, and release of 5‐HT (Stahl, 1977). In spite of those similarities, these two systems differ concerning metabolizing enzymes, and platelets are not competent to synthesize 5‐HT because of the absence of tryptophan hydroxylase (Kostanjšak & Zdunić, 2017; Stahl, 1985). In consideration of psychopathology, previous studies have shown lower 5‐HT levels in the platelets of patients suffering from depression (Kostanjšak & Zdunić, 2017; Maurer‐Spurej et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors such as neuropeptides, neurotransmitters, opioids, growth factors, cytokinesis, adipokinesis, and battery ligands modulate the release of adrenal glucocorticoids independently of pituitary adrenocorticotropic hormone (ACTH) ( 13 ). Adrenal cortisol release during circadian ascension and stress response are under the control of ACTH and preganglionic sympathetic neurons ( 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytes are reported to produce mood-modulating serotonin. Thrombocytes and basophilic granulocytes cell counts are known to be associated with positive and negative moods via histamine and serotonin interactions [8, 44]. In addition, thrombocyte cell count is also found to be related to mood disorders such as bipolar affective disorder [6, 45].…”
Section: Discussionmentioning
confidence: 99%